PENERAPAN MODEL STAD BERBASIS GAMIFIKASI UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Nurul Wahida; Yenni Fitra Surya; Sumianto; Mufarizuddin; Nurmalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low problem-solving ability of fifth-grade students, especially in mathematics learning. This research aims to improve the problem-solving ability of class V-A students at UPT SDN 001 Air Tiris. The low problem-solving ability can be improved by using the STAD model based on gamification. This research is a classroom action research, conducted in two cycles and each cycle consists of two meetings. The subjects in this study were 20 students and the observers were the class V-A teacher and peers, while the object was using the STAD model based on gamification to improve students' problem-solving ability. The research instruments consisted of observation sheets of teacher and student activities, test sheets, and documentation sheets. Meanwhile, the data analysis techniques used were qualitative and quantitative. Based on the results of the research conducted through two cycles, in cycle I meeting I the students' problem-solving ability was in the very poor category 45%, and meeting II was in the very poor category 55%. Whereas in cycle II meeting I the students' problem-solving ability was in the poor category 65% and in meeting II in the very good category 90%. Based on these results, it shows that using the STAD model based on gamification can improve the problem-solving ability of class V-A students at UPT SDN 001 Air Tiris.